Prevalence of oral mucosal lesions and associated risk factors in a Norwegian adult population – the HUNT4 Oral Health study - Thomas R. Klimowicz; Astrid J. Feuerherm; Wenche Moe Thorstensen; Lars M. Berg; Håkon Valen; Rune Becher; Abhijit Sen (BMC Oral Health)
Abstract Background Most studies on the prevalence of oral mucosal lesions (OMLs), including those from Norway, focus on patient populations. This study aimed to estimate the overall prevalence of OMLs and its types across different age groups and to examine their association with selected risk factors in a general adult population of Norway. Methods This cross-sectional study included a random sample of 4,909 individuals aged 19 years and older who completed questionnaires and underwent a standardized clinical examination for OMLs in the HUNT Oral Health Survey (2017–2019). The classification of OMLs was based on the World Health Organization and NHANES III guidelines. Odds Ratio (OR) with 95% confidence intervals (CI) were calculated using multivariable logistic regression to assess associations between OMLs and potential risk factors, adjusting for relevant confounders. Results The overall prevalence of OMLs was 7.5%, with a higher proportion observed in individuals aged 60 and older. The most prevalent oral lesions were exophytic lesions (3.1%) and white lesions (1.5%). Notably, individuals with a low/middle level of education had higher odds of having an OMLs than those with a higher level of education (OR, 1.27, 95% CI: 1.00-1.61) in the fully adjusted model. Exploratory analyses of lesion types found a positive association between smoking status and white lesions (OR, 1.77, 95% CI:1.05–2.97), as well as between a history of cancer and red-blue lesions (OR, 2.17, 95% CI, 1.14–4.11). Conclusion In this population-based study, 7.5% of Norwegian adults had one or more OMLs, with higher prevalence in participants aged 60 years and older. Further research is needed to confirm these findings in similar populations.